Prospek Pengembangan Rehabilitasi Tanaman Kakao dengan Teknik Sambung Samping untuk Meningkatkan Produksi dan Pendapatan Petani di Kecamatan Aere Kabupaten Kolaka Timur - Ramadhan, Syahrul; Saediman, H.; Rosmawaty, Rosmawaty (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2021)
This study aimed to assess the prospects for cocoa rehabilitation using side-grafting techniques to increase the production and income of farmers in the Aere Sub-district, East Kolaka District. The research was undertaken from March to April 2019 in Three villages, namely Aere, Tinete, and Rubia villages, selected purposively as study locations as they had large cocoa farming sizes and had applied side-grafting. Seventy-one respondents were selected from the population of 248 farmers. Data analysis employed an R/C ratio and descriptive statistics. Study results showed that cocoa rehabilitation prospects using a side-grafting technique in the study area were highly prospective. Cocoa farming was financially feasible, with the average income per cocoa farmer being IDR7,105,613 per year or IDR4,588,482 per ha per year. The R/C ratio of 2.0 meant that rehabilitation with side-grafting techniques to increase the production and income of cocoa farmers was financially feasible. Qualitative analysis also showed that the rehabilitation was feasible from technical, socio-cultural, and environmental aspects. The government was also committed to developing cocoa farming through the adoption of some policies and programs, including budget support